Analysis and application of Voronoi diagram - Rupšys, Petras (Lietuvos matematikos rinkinys, 2003)
In this paper an algorithm for constructing Voronoi diagram is given. Efficiency of the algorithm is investigated by the Monte Carlo simulation method. The Voronoi diagram is applied in the field of forestry.